Drug-coated Balloon : A Superb Alternative To Coronary Stents (Bangladesh Journal of Medicine, 2024)
The evolution of interventional cardiology has witnessed a paradigm shift in the management of coronary arterydisease (CAD). Among the arsenal of interventions, coronary stents have been a cornerstone, providing mechanicalsupport and reducing restenosis rates. However, concerns persist regarding stent-related complications such asin-stent restenosis, late stent thrombosis & hazards of bleeding due to use of long dual antiplatelet (DAPT). Inrecent years, the emergence of drug-coated balloon (DCB) has introduced a promising alternative approach forthe treatment of CAD. DCB offer a unique mechanism of action, delivering antiproliferative drugs directly to thevessel wall without leaving a permanent implant. This characteristic eliminates concerns related to stent thrombosisand the need for long-term DAPT. Furthermore, DCB preserve vessel anatomy and vasomotion, potentially enablingfuture revascu- larization options. Clinical trials and real-world data have demonstrated the efficacy of DCB invarious coronary lesions, including small vessels and in-stent restenosis. This abstract provides an overview ofthe advantages of DCB over traditional coronary stents and highlights key clinical evidence supporting their use.Additionally, it discusses the economic implications and patient-centered outcomes associated with DCB therapy.Despite these advantages, challenges such as device delivery and optimal drug formulations remain areas ofongoing research and development. In conclusion, DCB represent a superb alternative to coronary stents inselected patients with CAD, offering comparable efficacy while mitigating stent & antiplatelet related complications.As technology continues to advance, further refinements in DCB design and drug delivery systems hold thepotential to revolutionize the landscape of coronary intervention, providing safer and more effective treatmentoptions for patients with CAD.Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 151